Coumarin-Oxadiazole Derivatives: Synthesis and Pharmacological Properties - Abdul Razak, Nurhayatun S.; Jamalis, Joazaizulfazli; Chander, Subhash; Wahab, Roswanira A.; Bhagwat, Deepak P.; Smith, Terry K.; Sankaranarayanan, Murugesan (Mini-Reviews in Organic Chemistry, 2020)
Coumarin and oxadiazole moieties ubiquitously occur in a wide range of natural products and are valued for their varied and beneficial pharmacological activities. Herein, this review focuses on various documented techniques used by researchers to synthesize an assortment of biologically active coumarin-oxadiazole scaffolds. Also, the common techniques discussed are used to establish the wide-range of biological activities of the synthesized coumarin and oxadiozole derivatives, including; antioxidant, anthelmintic, antimicrobial, anti-tuberculosis, analgesic, anti-inflammatory, cytotoxicity and anticonvulsant. Additionally, the current, well-established drugs synthesized using coumarin-oxadiazole scaffolds are typically dispensed in regular clinical practice are also highlighted in this review paper.
Keywords: drugs